A basic review on systemic treatment options in WHO grade II-III gliomas. (January 2021) - Mair, Maximilian J.; Geurts, Marjolein; van den Bent, Martin J.; Berghoff, Anna S.
Highlights: WHO grade II-III gliomas are rare primary central nervous system tumors. Adjuvant treatment is needed as most tumors recur after resection. Interpretation of clinical trials is complicated due to recent changes in glioma classification. Radiotherapy in combination with chemotherapy (PCV or temozolomide) were investigated in clinical prospective trials. A watch-and-wait approaach may be justified in some patients. Abstract: WHO grade II-III gliomas are rare primary brain tumors occurring at a median age of about 35–55 years. Median survival is longer in WHO grade II-III glioma compared with WHO grade IV glioblastoma as survival times of up to 10 years and longer can be observed. Maximal safe resection and adjuvant therapies including chemotherapy and radiotherapy are the mainstay of treatment. Clinical trials in WHO grade II-III tumors are challenging due to the rarity and the long follow up times. The 2016 WHO Classification of Central Nervous Tumours introduced a new diagnostic framework relying on molecular characteristics, providing the definition of prognostically more homogenous subgroups compared to the histopathological analysis. Most available evidence on the adjuvant treatment of WHO II-III gliomas was generated in the pre-molecular era, challenging the interpretation of study results. The present review therefore summarizes the available data from prospective trials on systemic treatment options in WHO grade II-III glioma, considering molecular markers, recently published results and future outlooks in the field.